Executory Power Of Fiduciary Guarantee Certificate In Consumer Financing Agreement Based On Law Number 42 Of 1999 Concerning Fiduciary Guarantee - Livia Kris Imani; Angelica Riza Claudya; Nurmala Pitaloka; Edhi Setiawan (Jurnal Indonesia Sosial Teknologi, 2023)
Based on the discussion, it can be seen that the legal arrangements in financing agreements with fiduciary guarantees are subject to the Civil Code by the terms of the validity of Article 1319, Article 1320, and Article 1338 agreements, as well as the provisions in Presidential Decree 61 of 1988 concerning Financing Institutions and Presidential Regulation No. 9 of 2009 concerning Financing Institutions. Legal protection for consumers due to the sale of fiduciary guarantee objects in financing agreements is that they must not violate the principles of consumer protection and provide legal certainty and legal protection for those interested and guarantees, primarily related to consumer rights and the sale of objects that are objects of fiduciary guarantee by Law Number 42 of 1999 concerning Fiduciary Guarantees agreed by the fiduciary grantor and recipient. The judge's legal consideration in the Decision of the Supreme Court of the Republic of Indonesia Number 441 K / Pdt.Sus-BPSK / 2019 is the legal relationship between consumers and finance companies, namely financing agreements so that if one party does not fulfill or violate the agreement, it causes an act of breach of promise/default; when there is a default, the withdrawal or execution must be by the decision of the Constitutional Court, but if there are actions outside the procedural such as coercion and violence, then would be against the law.